Study of Determine Manning Roughness Coefficient, n in Kampung Parit Jelutong Drainage - Jamal, Muhammad Syahmie; Md Ali, Zarina (Recent Trends in Civil Engineering and Built Environment, 2024)
Rivers have ever-changing characteristics that are influenced by the effects of human activities and are highly likely to face problems such as river erosion and sedimentation. The objectives of this study were to measure drainage characteristics and flow rates in selected drains, plot the flow rates along the drainage and determine the values ​​of roughness coefficients, n and flow conditions based on Froude number calculations. 5 series of measurements were carried out to determine drainage characteristics and profiles based on altitude datum level, flow rate data, wet perimeter, hydraulic radius and drainage slope angle. Measurement of flow velocity, depth, width and cross -sectional characteristics of the river to obtain the value of n. The range of n values ​​obtained from 0.0138 to 0.0272 and were classified as surfaces having gravel as well as shotcrete. The range of flow rate values ​​is between 0.025 m3/s to 0.068 m3/s. The Froude number obtained ranged from 0.0995 to 0.068 and was classified as a sub-critical flow because the Froude value was less than 1. Suggestions for improvement for the future are to add a few more sections along the drainage to get more accurate results and add a cross division in each section